Improving the Response Time of Online Letter Management Application Users: an Application of Social Representation Theory of Shame - Marzal, Jefri; Budiman, Wahyu; Adrefiza, -; Hutabarat, Benetika F.; Kurniawan, Wawan (Society of Visual Informatics, 2021)
One of the most important and potential problems encountered in an official online letter management application is the recipients' late response. This action research aims to improve the recipients' response time and determine the central core of shyness according to response time categories: less than 24 hours (green zone); between 24 hours to 48 hours (orange zone); and more than 48 hours (red zone) in managing formal online letter management system at Jambi University. Using the social representation theory of shyness as the basis of action adopted from Moscovici theory [1], it is hypothesized that response time displaying will impact response time improvement. A survey questionnaire distributed to 129 respondents showed a significant improvement in the participants' response time, respectively, in cycles 1 and 2. The zone group increased percentage sed from 22.44% to 52.49 % in the first cycle, and it ultimately raised to 62.38% at the end of the second cycle. Such an increase might be due to the users' efforts to avoid the level of shyness, which were classified into: (1) slow to respond and (2) personal or work unit late response time – both marked in red. It is recommended that social shyness incorporated in improving response time in a formal online letter can be further implemented with other social and psychological parameters. The application will illustrate computer systems' interaction on social society to implement regulations both in institutions and in government.